The Impact of Metacognitive Awareness on Retention of Solubility and Solubility Product Equilibrium Concepts - Marisa; Erlina; Ulfah, Maria (Hydrogen: Jurnal Kependidikan Kimia, 2025)
This study aims to describe the level of metacognitive awareness and learning retention regarding the concepts of solubility and solubility product among grade XI students at Senior High School 10 Pontianak, as well as to analyze the correlation between the two variables. The study population consisted of 94 students from classes XI A, XI B, and XI C, with a sample of 57 students selected through simple random sampling from classes XI B and XI C. Data were collected using a Metacognitive Awareness Inventory (MAI) questionnaire to measure metacognitive awareness and an essay test to assess learning retention. Descriptive and inferential statistical techniques were used for data analysis. The results showed that 35% of students demonstrated metacognitive awareness in the "developed" level, while 65% were in the "very well-developed" level. The average learning retention rate for solubility and solubility product concepts was 90.50%, categorized as high. A weak positive and significant correlation (r = 0.280) was found between metacognitive awareness and learning retention, with metacognitive awareness accounting for 7.8% of the variance in learning retention. These findings suggest that while metacognitive awareness influences learning retention to some extent, other factors also play a significant role. This study offers a contribution by specifically exploring the relationship between metacognitive awareness and learning retention on chemistry concepts such as solubility and Ksp concepts at the Senior High School level, a study and subject matter that is rarely explored specifically and simultaneously.